Caracterização clínico-demográfica e manejo clínico da infecção pelo vírus respiratório sincicial em crianças menores de cinco anos de idade atendidas no Hospital de Clínicas de Uberlândia, MG - Calegari, Tatiany (2008)
Objective: Perform the characterization of clinical and demographic profile of children less than five years old with infection caused by the respiratory syncytial virus (RSV) attended at the Hospital de Clínicas de Uberlândia and also the type of treatment and the clinical management. Methods: Four hundred and thirty six nasopharyngeal aspirate samples were collected from April 2000 to March 2007 of children less than five years old who presented acute respiratory infection (ARI). The RSV was diagnosed by the immunofluorescence assay (IFA). The information from the chart of patients with RSV positive cases had been collected for the identification of the clinical management. Results: Of the 436 samples collected 119 (27,3%) were positive for RSV by IFA. RSV circulation was predominant from March to May. The male gender corresponded to 58.8% of the patients. The median of age found was two months, being that the children less of one year old (78.1%) had the greater rate of infection. Seventy five patients had been hospitalized in a period among one and 63 days and the average of this period was 12.1 days. Fifty four children had base illness (congenital heart disease, lung disease and prematurity) and 46 required hospitalization. The clinical diagnoses were bronchiolitis (52.9%), upper respiratory tract infection (27.7%), pneumonia (11.8%) e bronchitis (7.6%). There was a significant association between the diagnoses of bronchiolitis and the age less of one year, and that group of children had the highest number of hospitalizations. In relation to clinical management of children hospitalized with bronchiolitis: 21,4% of the patients required mechanical ventilation, 94,6% needed the use of supplemental oxygen, 48,2% used antibiotics, 50,0% used corticosteroids, 83,9% used bronchodilators e 60,7% used antipyretic. There was one death. Conclusions: The RSV is responsible for respiratory illness in children less than one year old. For the patients with bronchiolitis, the values of hospitalization and submission to the mechanical ventilation had been higher to the ones found in literature. Bronchodilators, corticosteroids and antibiotics were given for children with viral ARI, however, it does not have consensus on effectiveness of these treatments.